Biological synthesis of cationic gold nanoparticles and binding of plasmid DNA - Raju, D.; Vishwakarma, Rishi K.; Khan, Bashir Mohammad; Mehta, Urmil J.; Ahmad, Absar (Materials Letters, 2014)
Nanobiotechnology is the development of eco-friendly experimental processes for the synthesis of nanomaterials. The present work focuses on synthesis of cationic gold nanoparticles (C-GNPs) for biological applications, especially in gene and drug delivery studies. A biosynthesis methodology has been developed for the functionalization of gold nanoparticles to cationic nature. The synthesis of C-GNPs was done by using peanut leaf extract in the presence of cysteamine. The formed C-GNPs were characterized by using UV-visible spectroscopy (UV-vis), the particles sizes and shapes were confirmed by a Transmission electron microscope (TEM) and crystallinity of C-GNPs was characterized by diffraction. The binding of plasmid DNA on the C-GNPs was confirmed by agarose gel electrophoresis. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Biomaterials; Cationic; Nanoparticles; Plasmid DNA; synthesis; TEM

Bacopa monniera recombinant mevalonate diphosphate decarboxylase: biochemical characterization - Shakeel Abbassi; Vishwakarma, Rishi K.; Patel, Parth; Kumari, Uma; Khan, Bashir Mohammad (International Journal of Biological Macromolecules, 2015)
Mevalonate diphosphate decarboxylase (MDD; EC 4.1.1.33) is an important enzyme in the mevalonic acid pathway catalyzing the Mg2+-ATP dependant decarboxylation of mevalonate 5-diphosphate (MVAPP) to isopentenyl diphosphate (IPP). Bacopa monniera recombinant MDD (BmMDD) protein was overexpressed in Escherichia coli BL21 (DE3) strain and purified to apparent homogeneity. K-m and V-max for MVAPP were 144 mu M and 52 U mg(-1) respectively. The values of turnover (k(cat)) and k(cat)/K-m, for mevalonate 5-diphosphate were determined to be 40 s(-1) and 2.77 x 10(5) M-1 s(-1) and k(cat) and k(cat)/K-m values for ATP were found to be 30 s(-1) and 2.20 x 10(4) M-1 s(-1), respectively. pH activity profile indicated the involvement of carboxylate ion, lysine and arginine for the activity of enzyme. The apparent activation energy for the BmMDD catalyzed reaction was 12.7 kJ mol(-1). Optimum pH and temperature for the forward reaction was found to be 8.0 and 45 degrees C. The enzyme was most stable at pH 7 at 20 degrees C with the deactivation rate constant (K-d(*)) of 1.69 x 10(-4) and half life (t(1/2)) of 68 h. The cation studies suggested that BmMDD is a cation dependant enzyme and optimum activity was achieved in the presence of Mg2+. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Mevalonate diphosphate decarboxylase; pH activity profile; Phylogenetic analysis; stability

Biochemical characterization of recombinant mevalonate kinase from Bacopa monniera - Kumari, Uma; Vishwakarma, Rishi K.; Sonawane, Prashant; Shakeel Abbassi; Khan, Bashir Mohammad (International Journal of Biological Macromolecules, 2015)
Mevalonate kinase (MK; ATP: mevalonate 5-phosphotransferase; EC 2.7.1.36) plays a key role in isoprenoid biosynthetic pathway in plants. MK catalyzes the phosphorylation of mevalonate to form mevalonate-5-phosphate. The recombinant BmMK was cloned and over-expressed in E. coli BL21 (DE3), and purified to homogeneity by affinity chromatography followed by gel filtration. Optimum pH and temperature for forward reaction was found to be 7.0 and 30 degrees C, respectively. The enzyme was most stable at pH 8 at 25 degrees C with deactivation rate constant (Kd*) 1.398 x 10(-4) and half life (t(1/2)) 49 h. pH activity profile of BmMK indicates the involvement of carboxylate ion, histidine, lysine, arginine or aspartic acid at the active site of enzyme. Activity of recombinant BmMK was confirmed by phosphorylation of RS-mevalonate in the presence of Mg2+, having K-m and V-max 331.9 mu M and 719.1 pKat mu g(-1), respectively. The values of k(cat) and k(cat)/K-m for RS-mevalonate were determined to be 143.82 s(-1) and 0.43332 M-1 s(-1) and k(cat) and k(cat)/K-m values for ATP were found 150.9 s(-1) and 1.023 M-1 s(-1). The metal ion studies suggested that BmMK is a metal dependent enzyme and highly active in the presence of MgCl2. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Bacopa monniera; Enzyme kinetics; Mevalonate kinase; stability